Pengaruh Religiusitas, Lokasi, dan Sosial Terhadap Minat Mahasiswa Memilih Program Studi Manajemen Bisnis Syariah: (Studi pada Mahasiswa Strata 1 Manajemen Bisnis Syariah UIN Raden Mas Said Surakarta) - Nur Romadhon, Farkhan; Walyoto, Sri (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2024)
The aim of this research is to examine the influence of Religiosity, Location and Social Affairs on Students' Interest in Choosing a Sharia Business Management Study Program (Study of Undergraduate Students in Sharia Business Management at UIN Raden Mas Said Surakarta). This research uses a population of students from Surakarta. The sample was selected using a non- probability sampling method, totaling 300 respondents by distributing questionnaires online using Google Form. The analysis technique used was multiple linear regression. The results research are that there is a positive influence on Location and Social Affairs on Interest in Choosing a Sharia Business Management Study Program (Study for Undergraduate Students in Sharia Business Management at UIN Raden Mas Said Surakarta) while Religiosity has no influence. Keywords: Religiosity, Location, Social, and Interests